Effect of Limit-Fed Diets With Different Forage to Concentrate Ratios on Fecal Bacterial and Archaeal Community Composition in Holstein Heifers - Zhang, Jun; Shi, Haitao; Wang, Yajing; Cao, Zhijun; Yang, Hongjian; Li, Shengli (Frontiers in Microbiology, 2018)
Limit-feeding of a high concentrate diet has been proposed as an effective method for improving feed efficiency and reducing total manure output of dairy heifers; meanwhile the effects of these methods on hindgut microbiota are still unclear. This study investigated the effects of a wide range of dietary forage:concentrate ratios (F:C) on the fecal composition of bacteria and archaea in heifers using next-generation sequencing. Four diets with different F:C (80:20, 60:40, 40:60, and 20:80) were limit-fed to 24 Holstein heifers, and the fecal fermentation parameters and bacterial and archaeal communities were investigated. With increasing dietary concentrate levels, the fecal dry matter output, neutral detergent fiber content (NDF), and proportion of acetate decreased linearly (P < 0.01), while the fecal starch content and proportion of propionate, butyrate, and total branched-chain volatile fatty acids (TBCVFAs) were increased (P ≤ 0.05). An increased concentrate level linearly increased (P = 0.02) the relative abundance of Proteobacteria, and linearly decreased (P = 0.02) the relative abundance of Bacteroidetes in feces. At the genus level, the relative abundance of unclassified Ruminococcaceae and Paludibacter which may have the potential to degrade forage decreased linearly (q ≤ 0.02) with increasing dietary concentrate levels, while the relative abundance of Roseburia and Succinivibrio which may be non-ﬁbrous carbohydrate degrading bacteria increased linearly (q ≤ 0.05). Some core microbiota operational taxonomic units (OTUs) also showed significant association with fecal VFAs, NDF and/or acid detergent fiber (ADF) content. Meanwhile, the relative abundance of most detected taxa in archaea were similar across different F:C, and only Methanosphaera showed a linear decrease (P = 0.01) in high concentrate diets. Our study provides a better understanding of fecal fermentation parameters and microbiota under a wide range of dietary F:C. These findings support the potential for microbial manipulation by diet, which could enhance feed digestibility and relieve environmental problems associated with heifer rearing.